The Tacit OrganizationThe Tacit Organization, by IngersollVirginia H. and AdamsGuy B.. Greenwich, CT: JAI Press, 1992, 280 pp., $73.25, cloth. - Weeks, John R. (Academy of Management Review, 1994)
The article reviews the book ?The Tacit Organization,? by Virginia H. Ingersoll and Guy B. Adams.